(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Features of production process and growth of Achillea millefolium have been studied on flood plain meadows of the river Psell, which are used as pastures and for haymaking. Dynamics in the basic indicators of growth is described. Vitality structure in populations of Achillea millefolium is defined on basis of pascual and fenisicial gradients.